TSC22D4 promotes TGFβ1-induced activation of hepatic stellate cells - Sakurai, Minako; Weber, Peter; Wolff, Gretchen; Wieder, Annika; Szendrödi, Julia; Herzig, Stephan; Üstünel, Bilgen Ekim (Biochemical and biophysical research communications, 2022)
Non-alcoholic fatty liver disease (NAFLD), non-alcoholic steatohepatitis (NASH) and liver fibrosis emerge as progressive liver diseases that accompany metabolic syndrome usually characterized by obesity, insulin resistance and type 2 diabetes. Currently no FDA approved treatments exist for the treatment of NASH and liver fibrosis, which requires a better knowledge of the underlying molecular mechanisms. TSC22D4 belongs to the TSC-22 protein family, the members of which are regulated by inflammatory and stress signals. Interestingly, patients with type 2 diabetes, with NAFLD as well as with NASH all have elevated levels of hepatic TSC22D4 expression. Previous studies with targeted deletion of TSC22D4 specifically in hepatocytes showed that TSC22D4 not only acts as a critical controller of diabetic hyperglycemia, but also contributes to NAFLD/NASH progression. To gain better insight into the development of progressive liver diseases, here we studied the function of TSC22D4 in hepatic stellate cells (HSCs), which play a key role in the pathogenesis of liver fibrosis. Our results indicated that TSC22D4 contributes to TGFβ1-mediated activation of HSCs and promotes their proliferation and migration. RNA-Sequencing analysis revealed that TSC22D4 initiates transcriptional events associated with HSC activation. Overall, our findings establish TSC22D4 as a key hub in the development of liver fibrosis, acting across different cellular compartments. Combinatorial TSC22D4 targeting in both hepatocytes and HSC may thus show superior efficacy against progressive liver disease.
Gesehen am 28.11.2022